2005
DOI: 10.1063/1.2150273
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-controlled epitaxial strain in La0.7Sr0.3MnO3∕Pb(Mg1∕3Nb2∕3)O3-PbTiO3(001) films

Abstract: Epitaxially grown La0.7Sr0.3MnO3 thin films show resistance modulations induced by the inverse piezoeffect of the employed Pb(Mg1∕3Nb2∕3)O3-PbTiO3(001) (PMN-PT) substrates. The in-plane strain state of the films can continuously be tuned by application of a piezovoltage to PMN-PT. The lattice deformation of a PMN-PT(001) substrate was quantified by x-ray measurements under an electric field. Variation of in-plane lattice parameters by ∼0.06% reversibly changes the resistance of the manganite films by up to 9% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
132
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(136 citation statements)
references
References 11 publications
4
132
0
Order By: Relevance
“…In a previous work 12 we have shown that the epitaxial strain in ferromagnetic , this limit is not strict but was set for experimental reasons (voltage limit of 500 V across 0.4 mm thick crystals giving = E 12 kV cm -1 , avoidance of crack formation in the piezo-crystal). Note that reversible strain of similar magnitude is applied in mechanical bending experiments 20 , but the mechanical apparatus makes bending less versatile than piezoelectric strain control for some experiments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous work 12 we have shown that the epitaxial strain in ferromagnetic , this limit is not strict but was set for experimental reasons (voltage limit of 500 V across 0.4 mm thick crystals giving = E 12 kV cm -1 , avoidance of crack formation in the piezo-crystal). Note that reversible strain of similar magnitude is applied in mechanical bending experiments 20 , but the mechanical apparatus makes bending less versatile than piezoelectric strain control for some experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Multiferroic composites are understood as a combination of a ferromagnetic and a ferroelectric compound in mixed-powder, layered or nanocolumnar geometries where the components are essentially elastically coupled 5,6,7,8,9,10,11,12,13 . The strain induced in one component (either by magnetostriction in the magnet or by inverse piezoelectric effect in the ferroelectric) is mediated to the other and alters its polarization (be it electric or magnetic).…”
Section: Introductionmentioning
confidence: 99%
“…25 Thiele et al have shown that voltagecontrolled epitaxial strain in LSMO is possible when exploiting the inverse piezoelectric effect of Pb(Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 (001) (PMN-PT) substrates. 26 They report on voltage-controlled changes of the Curie temperature in a LSMO film of 20 nm thickness between 278 K and 297 K. Fig. 1 displays the effect for the 20 nm thick LSMO sample reported in Ref.…”
mentioning
confidence: 99%
“…The most commonly used piezoelectric substrate is (1-x)Pb(Mg 1/3 Nb 2/3 )O 3 -xPbTiO 3 , which is a well-known relaxor ferroelectric material with excellent electromechanical and piezoelectric properties for compositions near the morphotropic phase 3 boundary (0.25  x  0.35) [12]. Piezoelectric strain transfer from PMN-PT substrates has, for example, been used to tune the magnetic properties of manganite [13,14], ferrite [15][16][17][18][19], and metallic magnetic films [20][21][22][23], to alter the electrical resistance of magnetic oxides [13,18,[24][25][26], to demonstrate straincontrolled light emission from semiconductor heterostructures [27,28], and to tailor the properties of graphene [29]. In addition, strain-modulation of magnetic properties on a microscopic scale has recently been demonstrated in ferromagnetic-ferroelectric hybrids [30][31][32], which has opened new ways to electric control of ferromagnetic domain formation and magnetic domain wall motion [33,34].…”
mentioning
confidence: 99%